The Influence of Social Media Marketing on Purchase Intention through Customer Experience - Maulana Iqbal N; Siska Ernawati Fatimah (PT FORMOSA CENDEKIA GLOBAL, 2026)
With customer experience serving as a mediating variable, this study attempts to investigate how social media marketing affects purchase intention among Indonesian marketplace users. A survey with 150 respondents was used in a quantitative manner. PLS-SEM was used to analyse the data obtained from a questionnaire given to active users in 2025. The results show that customer experience and purchase intention are greatly and favourably impacted by social media marketing. Additionally, purchase intention is significantly positively impacted by customer experience, which also partially mediates the link. These findings emphasize the necessity of delivering positive customer experiences to enhance marketing effectiveness.